Agricultura orgânica e atores neorrurais na Serra da Mantiqueira: o grupo Orgânicos da Mantiqueira, Gonçalves, MG - Aun, Nádia Jarouche (2012)
This paper discusses the characteristics of the new rural population and their forms of action, based on the case of the Orgânicos da Mantiqueira group, they are localized at Gonçalves, MG. It is intended to discuss the new forms of occupation in rural areas played by those new actors and the multiple functions assigned to them. Therefore It will be analyzed the construction of this new ruralities and the different ways of occupying a land marked by traditional customs. Within this context It will be underlined the differences between rural and urban occupation. The land occupation is approached from the concept of the agriculture multifuncionality. It will be taken into account the peculiarities of the new rural population s productive and organizational characteristics besides their interactions with local populations in rural reconstruction and the evaluation of the area through new ecologic agricultural basis. Starting from the history of the ecological movement in rural areas, the ecological agriculture is studied through the analysis of the agroecological conversion systems. There will be pointed out some relevant issues related to the crop systems management in the visited areas as well as the critical points affecting the realization of the Orgânicos da Mantiqueira s productive activity. It can be perceived at the end that the constitution of a group and its institutionalization upon society happens by collective desire and common objective considering, during its process, the emergence of new contradictions.